The New Geological Epoch, "Anthropocene," as a Result of Human Economic Activity - Viktor Ievdokymov; Oksana Oliinyk; Dymytrii Grytsyshen; Valentyna Ksendzuk; Galyna Nord (Comparative Economic Research. Central and Eastern Europe, 2018)
The impact of human economic activity on the environment and its irreversible changes. An interdisciplinary approach to the development of the economic system has been used in this paper due to the fact that the subject of the study goes beyond the functional economic sciences, and economics in general. The study is aimed at investigating the interaction of man, as an economic agent, and the environment. It has led to the study of research papers devoted to natural science, in particular, to changes in geological epochs, sustainable development and economic processes from the position of their influence on the environment. This allowed us to synthesize new economic knowledge about the importance of economic activity in the formation of the new geological epoch, "Anthropocene". Based on the results of the study, the influence of human economic activity on the environment in the light of the geological, technocratic and economic development of society has been proved. The scientific results which were obtained can be used in reforming national economic systems by adapting them to leading world concepts on sustainable development.
Keywords: Q01; O10; 330; sustainable development; human economic activity; transformation; "Anthropocene"; technocratic development